Florida Foliage House Plant Care: Spathiphyllum - Richard J. Henny; Jianjun Chen (EDIS, 2013)
Most Spathiphyllum are seen in flower when at market. The attractive white blooms, called spathes, are long lasting. With proper plant care, Spathiphyllum may produce blooms year after year. Spathiphyllum is a very attractive house plant even when not in bloom and adapts well to home and patio environments. This 2-page fact sheet was written by R. J. Henny and J. Chen, and published by the UF Department of Environmental Horticulture, June 2013.